Efforts to Improve Students' Gross Motor Skills Using The Low Impact Outbound Games at Sekolah Alam Bogor Kindergarten - Roslinawati, Nova; Wilson, George (Educational Researcher Journal, 2026)
This study aims to improve gross motor skills through low-impact outbound play activities at the Bogor Nature School Kindergarten, North Bogor. The subjects were 15 children in the playgroup at the Bogor Nature School Kindergarten, consisting of 7 boys and 8 girls. This research is a classroom action research using the Kemmis and McTaggart research design. This research was conducted in two cycles with the theme of Self-Identity. The research period was in the first semester. The data collected were descriptive qualitative and quantitative data. Descriptive qualitative data is a report of research results presented in the form of descriptions or learning processes. Meanwhile, quantitative data is learning outcomes presented in the form of tables or diagrams. The data obtained was then compared with success criteria to determine gross motor skills through low-impact outbound games. Based on the research results, it can be seen that 20% of children were able to carry out low-impact outbound game activities independently, namely from 66.6% in cycle 1 to 86.6% in cycle 2.